How to Achieve a Company's Vision Successfully through Strategy Implementation - Paatsalo, Tomi (My University, 2018)
Globalization, fast market change, and rapid technology evolution have led organizations to situations where they need to be ready to answer to that change. Vision is the base for this change. Changing direction means the ability of the strategy to adjust to quick change, corresponding to new needs. The strategy is a plan that seeks to achieve the target pursued - vision. Furthermore, strategic actions direct everyday operational level acts. Vision is a fundamental factor that every strategic action should be based on. Research is still lacking themes such as how companies’ personnel perceive vision and what kind of impact a vision has in personnel’s everyday work tasks. This study examines how personnel perceives vision, how the vision is affecting to employees and how the vision could be reached successfully through implementing strategies. Data is collected through interviews that present personnel’s voice about the vision, how it has changed the way they work and how the vision could be developed through strategies to achieve the vision successfully. The findings of this study show that vision is seen as an important issue but not concrete enough. The management teams and personnel’s answers differed from each other. Surprisingly, vision as a concept was not seen that important for management team when contrarily employees perceived it as a starting point for the whole company. Communication ambiguity about an individual or team-specific milestones, high-level of vision and lack of resources, were all factors that seemed to hinder a company’s journey towards the vision. Even though vision’s fundamental aim is not to provide practical steps to success, yet most of the informants were willing to see more guidelines which direct everyday actions towards the vision. For example, team-specific strategies and individual targets are one example of those, while the management team and the co-founder were willing to give autonomy to employees to find out the way to the vision.
Keywords: Vision; strategy; strategy change; implementation; reaching vision through strategies; fi=Johtaminen ja organisaatiot|en=Management and Organization|; fi=Master’s Programme in Strategic Business Development|